5+6(a-1)=36

Simple and best practice solution for 5+6(a-1)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6(a-1)=36 equation:



5+6(a-1)=36
We move all terms to the left:
5+6(a-1)-(36)=0
We add all the numbers together, and all the variables
6(a-1)-31=0
We multiply parentheses
6a-6-31=0
We add all the numbers together, and all the variables
6a-37=0
We move all terms containing a to the left, all other terms to the right
6a=37
a=37/6
a=6+1/6

See similar equations:

| `5-5x=24-8x | | `3x=25-2x | | X2-22x+850=0 | | -9x8+4x=28-2x•42 | | (2x-7)-(2x-4)=0 | | -y+3=2y | | 4(2x-3)+16=42 | | v2+22v+21=0 | | 3(1)x+4(1)x=6(0) | | 1/x+2/x-1=2/x(x-1) | | y/8=3/2 | | .25y=10 | | n/n-3+2=n/n-3 | | 4/5+n=2/3 | | -1/2+z=-5/3 | | x-2/3=5/7 | | y+2/3=14/3 | | 14=x+25 | | 8/x+22=2/3x | | 23+n=-81 | | n+9.7=4.6 | | -1/2+y=3/2 | | y-10.8=5.6 | | 3x-7=20+2x | | 6(x-1)+71=x-7(x+1) | | 6(x-1)+71=x-7(x=1) | | 7x-9=33+14x | | 3x-8x=9 | | 7-3x=5+4x+11-16 | | x+(x*2.5)=7500 | | 2x-11=5x-17 | | 1/3x+3=4+1/3x |

Equations solver categories